Direct Observation of Orbital Driven Strong Interlayer Coupling in Puckered Two‐Dimensional PdSe2. Issue 9 (17th January 2022) - Ryu, Jung Hyun; Kim, Jeong‐Gyu; Kim, Bongjae; Kim, Kyoo; Kim, Sooran; Park, Jae‐Hoon; Park, Byeong‐Gyu; Kim, Younghak; Ko, Kyung‐Tae; Lee, Kimoon
Abstract: Interlayer coupling between individual unit layers is known to be critical in manipulating the layer‐dependent properties of two‐dimensional (2D) materials. While recent studies have revealed that several 2D materials with significant degrees of interlayer interaction (such as black phosphorus) show strongly layer‐dependent properties, the origin based on the electronic structure is drawing intensive attention along with 2D materials exploration. Here, the direct observation of a highly dispersive single electronic band along the interlayer direction in puckered 2D PdSe2 as an experimental hallmark of strong interlayer couplings is reported. Remarkably large band dispersion along the k z ‐direction near Fermi level, which is even wider than the in‐plane one, is observed by the angle‐resolved photoemission spectroscopy measurement. Employing X‐ray absorption spectroscopy and density functional theory calculations, it is revealed that the strong interlayer coupling in 2D PdSe2 originates from the unique directional bonding of Pd d orbitals associated with unexpected Pd 4 d 9 configuration, which consequently plays a decisive role for the strong layer‐dependency of the band gap. Abstract : Unique large interlayer coupling triggered by the directional orbitals is firstly observed through both angle‐resolved photoemission spectroscopy and first principles calculations. Direct and comprehensive experimental/theoretical analyses provide a clear explanation of the strong layer number dependency of band gap and electronic dispersion in 2D PdSe2, which is an unsolved puzzle in representative 2D systems.